Influence of Defects to Zr65Cu18Ni7Al10 Bulk Metallic Glass Properties Under Dynamic Compression - Zhang, C.; Zhou, D.; Hou, B. (Frontiers in Materials, 2022)
The Zr65Cu18Ni7Al10 bulk metallic glass with smaller diameter exhibits higher fracture strength under dynamic compression, which is ascribed to concentration of flow defect. The density of shear bands in the sample surface will increase with decreasing of the diameter, whereas, average distance and width of tear ridges in the fracture surface will increase with larger diameter. In addition, the volume of shear transformation zone can be estimated, which presents a ductile-to-brittle transition with the change of diameter. The physical graph of shear transformation zone can be obtained from the experimental analysis.